Solve for n n+(n-2)+(n-4)+(n-6)=-72

Math
n+(n-2)+(n-4)+(n-6)=-72
Simplify n+n-2+n-4+n-6.
Tap for more steps…
Add n and n.
2n-2+n-4+n-6=-72
Add 2n and n.
3n-2-4+n-6=-72
Add 3n and n.
4n-2-4-6=-72
Simplify by subtracting numbers.
Tap for more steps…
Subtract 4 from -2.
4n-6-6=-72
Subtract 6 from -6.
4n-12=-72
4n-12=-72
4n-12=-72
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 12 to both sides of the equation.
4n=-72+12
Add -72 and 12.
4n=-60
4n=-60
Divide each term by 4 and simplify.
Tap for more steps…
Divide each term in 4n=-60 by 4.
4n4=-604
Cancel the common factor of 4.
Tap for more steps…
Cancel the common factor.
4n4=-604
Divide n by 1.
n=-604
n=-604
Divide -60 by 4.
n=-15
n=-15
Solve for n n+(n-2)+(n-4)+(n-6)=-72

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top